2017
DOI: 10.48550/arxiv.1705.05482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black holes, hidden symmetries, and complete integrability

Valeri P. Frolov,
Pavel Krtous,
David Kubiznak

Abstract: The study of higher-dimensional black holes is a subject which has recently attracted vast interest. Perhaps one of the most surprising discoveries is a realization that the properties of higher-dimensional black holes with the spherical horizon topology and described by the Kerr-NUT-(A)dS metrics are very similar to the properties of the well known four-dimensional Kerr metric. This remarkable result stems from the existence of a single object called the principal tensor. In our review we discuss explicit and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 278 publications
(526 reference statements)
0
43
0
Order By: Relevance
“…The dynamics of test particles in rigidly rotating spacetime backgrounds is essentially affected by the appearance of gravitoelectromagnetic fields at the classical and quantum levels. For special values of the parameters of such and similar systems, classical dynamics of test particles can be completely integrable due to appearance of hidden symmetries, which also reveal themselves in peculiar properties of the corresponding quantum systems [5,6,10,11,12,17,39]. This section aims to investigate such effects for geodesic motion in a rotating conical background.…”
Section: Dynamics In Rigidly Rotating Spacetimesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of test particles in rigidly rotating spacetime backgrounds is essentially affected by the appearance of gravitoelectromagnetic fields at the classical and quantum levels. For special values of the parameters of such and similar systems, classical dynamics of test particles can be completely integrable due to appearance of hidden symmetries, which also reveal themselves in peculiar properties of the corresponding quantum systems [5,6,10,11,12,17,39]. This section aims to investigate such effects for geodesic motion in a rotating conical background.…”
Section: Dynamics In Rigidly Rotating Spacetimesmentioning
confidence: 99%
“…The very well known examples where the geometry effects essentially on the symmetry properties of the particle systems are provided by the integrable dynamics of a test particle in the Kerr black hole due to the Carter integral [5], and the enhanced supersymmetry that characterizes the motion of a spinning particle in a Kerr-Newman black hole [6]. In these two cases we are dealing with hidden symmetries and the so-called Killing and Killing-Yano tensors associated with them [7,8,9,10,11,12]. Other effects related with geometry are the Lense-Thirring effect produced by gravitoelectromagnetic fields [13,14] and the production of additional particles in quantum field theories in curved spaces [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Principal tensors are very interesting quantities. As reviewed in [15], they have applications in the Kerr-NUT-AdS and Kerr-NUT-dS families, as well as in another set of spacetimes with Lorentzian signature with a principal tensor built from eigenvalues with null gradient, an issue that it is far from being fully understood, and is currently an open problem [14].…”
Section: Proca Field Perturbations In Schwarzschild-ads: the Fkks Met...mentioning
confidence: 99%
“…Massive vector fields were considered not only under a small rotation approximation with the equations yielding a ladder of coupled multipoles [9], but also without approximations using a fully numerical approach [10,11]. In a different development, and following previous work [12][13][14][15][16] that takes into account the presence of the principal tensor in the Kerr-NUT-AdS and Kerr-NUT-dS spacetimes, i.e., spacetimes describing a rotating black hole in four and in higher dimensions and that include the NUT parameters and a cosmological constant, Frolov, Krtouš, Kubizňák, and Santos [17], or FKKS for short, were able to extend the perturbation analysis to the case of a Proca massive vector field in spinning geometries. It was further shown that with this formalism the Proca equations can be separated.…”
Section: Introductionmentioning
confidence: 99%
“…( 15), ( 17), (18) as an example of a generalised Killing pair. Contracting (15) with p i p j p k , one obtains its Hamiltonian counterpart ξ (1) , p { η (1) , p , H} − η (1) , p { ξ (1) , p , H} − ξ (1) , p { ξ (1) , p , H} = 0.…”
Section: Two-dimensional Examplesmentioning
confidence: 99%